Aplikasi Sistem Informasi Geografis untuk Zonasi Kawasan Hutan Berdasarkan Kementrian Kehutanan dan Kemampuan Lahan di Kabupaten Bandung - Iskandar Muda Purwaamijaya (Forum Geografi, 2012)
The main objectives in the geographic information system applications for zoning of forest areas based on the ministries of forestry and land capability is to determine the broad allocation of forest land in Bandung Regency based on Ministerial Decree 79/2001 on the basis of analysis with analytical capabilities of BPDAS land so as to provide a common perception in spatial planning and resource management natural resources in Bandung Regency. Research is done by quantitative method using Geographic Information System. Area difference of forest zone based on Ministerial Decree 79/2001 to BPDAS land capability is 69,709.009 ha or 26.042 kms and 26.042 kms. The result of research providing recommendations to decision makers in Bandung Regency associated with the analytical model and the Ministerial Decree 79/2001 SK model BPDAS analysis of land capability so that spatial planning and management of natural resources can be more synergistic to achieve sustainable development that takes into account the principles sustainable principles, optimal, harmonious and balanced.